Rational synthesis and comparative investigation on a series of fluorinated aryl substituted diketopyrrolopyrrole. Issue 5 (2nd February 2017) - Xu, Jie; Zhang, Shaoze; Wu, Shengying; Bi, Shiming; Li, Xinjin; Lu, Yunxiang; Wang, Limin
Abstract: We novelly designed and synthesized a set of fluorinated diphenyl-diketopyrrolopyrrole (DPP) compounds by varying the position and amount of fluorine atom, and to the best of our knowledge, it is the first time a difluoromethyl group and perfluoroalkyl chains had been introduced into the DPP unit in good yields. We investigate the optical/electrochemical properties of all the compounds. Density functional theory (DFT) calculations were applied to explore orbital energy value of these compounds. The results demonstrated that the perfluorocarbon chains substituted DPPs with larger red-shift in both absorption and emission spectra and narrower bandgap. Graphical abstract: